International job search: Mexicans in and out of the US - Sílvio Rendón; Alfredo Cuecuecha (Institute for the Study of Labor (IZA), 2007)
It is argued that migration from Mexico to the US and its corresponding return migration are determined by international wage differentials and preferences for origin. We use a model of job search, savings and migration to show that job turnover is a crucial determinant of the migration process. We estimate this model by Simulated Method of Moments (SMM) and find that migration practically disappears if Mexico has American arrival rates while employed. Doubling migration costs reduces migration rates in half, while subsidizing return migration in 300 reduces migration rates of older migrants but increases migration rates of younger migrants.
Keywords: F22; 330; International migration; job search; job turnover; savings; structural estimation; Internationale Arbeitsmobilität; Einwanderung; Rückwanderung; Mexikaner; Arbeitsuche; Sparen; Migrationstheorie; Schätzung; USA; Mexiko